The relationship between peak muscle oxygen consumption and muscle oxygenation recovery time after submaximal exercise - Ichimura, S.; Moriguchi, T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
We investigated the relationship between pulmonary and muscle oxygen consumption (mVO2) and the muscle oxygenation recovery time after exercise to establish a convenient method with less onerous for subjects during estimating the muscle oxygen capacity. Methods: Subjects were seven healthy male volunteers (age 26±6yrs; height 169.4±6.7cm; weight 66.0±9.3kg) performed the dynamic knee extension and cycling exercise with stepwise incremental load method. The exercise load during dynamic knee extension exercise was started at 24watts and increased by 12watts every 6 minutes including 3 minutes recovery time (3min Ex + 3min Rec). That during cycling exercise was started at 60watts and increased by 30watts every 6 minutes within 3 minutes recovery time. The each exercise was performed until the subjects reached exhaustion and was performed the twice to evaluate the mVO2 and muscle oxygenation recovery time, respectively. Pulmonary O2 uptake and CO2 output (AE-280, Minato) and muscle oxygenation at the vastus lateralis using nearinfrared spectroscopy (HEO-200, Omron) were measured. We performed arterial occlusion on upper thigh proximal to the measurement sites before the start of the exercise for 3 minutes and repeated arterial occlusion immediately after each exercise load for 1 minute to evaluate the mVO2 at rest and during each exercise load during estimating the mVO2 (Hamaoka et al. 1996 JAP). The muscle oxygenation recovery time was evaluated the using the half recovery time of muscle oxygenation (T1/2reoxy) (Ichimura et al. 2006). Results: Pulmonary O2 uptake, CO2 output and mVO2 were increased with the increased load during dynamic knee extension exercise and cycling exercise. In dynamic knee extension exercise, the value of CO2 output was significantly higher than that of O2 uptake during 63% of peak workload. In cycling exercise, the value of CO2 output was significantly higher than that of O2 uptake during 73.7% of peak workload. T1/2reoxy in dynamic knee extension exercise and cycling exercise were not significant increased since 63% and 73.7% of workloads, respectively although the increase of the T1/2reoxy observed with increased load. In dynamic knee extension exercise, there was an inverse correlation between the peak mVO2 and the T1/2reoxy after peak workload exercise (r=-0.849, p<0.05). It was observed the tendency of an inverse correlation between the peak mVO2 and the T1/2reoxy during 63% of peak workload (r=-0.726, p=0.06). In cycling exercise, the inverse correlation between the peak mVO2 and the T1/2reoxy after peak workload exercise (r=-0.881, p<0.05) and 73% of peak workload exercise (r=-0.823, p<0.05) were observed. The value of peak oxygen uptake also inverse correlated with T1/2reoxy after peak workload exercise (r=-0.941, p<0.01) and 73% of peak workload exercise (r=-0.930, p<0.01). Conclusion: We found that the T1/2reoxy after maximal exercise relate to the peak mVO2, as well as that after submaximal exercise intensities corresponding to the ventilator threshold.